A Review of Trends in the Scope of International Scholarship in Middle Level Education, 1989–2019 - David C Virtue; Cheryl R Ellerbrock; Katherine M Main (Middle Grades Review, 2020)
Middle level education as a field of study has expanded during the last thirty years to include a growing, international knowledge base. The primary purpose of this review essay is to highlight trends in the extent to which refereed scholarship in the field of middle level education has reflected international content and perspectives during the last thirty years. To accomplish this task, the authors conducted a chronological review of the major refereed publications of the Association for Middle Level Education, Adolescent Success, and the American Educational Research Association (AERA) Middle Level Education Research (MLER) SIG as well as Middle Grades Research Journal and Middle Grades Review. The authors also examined AERA conference programs between 2010 and 2019 for international content and perspectives in MLER SIG sessions. While the authors’ primary aim was to understand trends in the geographic scope of scholarship in the field, they also gleaned tentative insights about research approaches, theoretical frameworks, and editorial bias that informed a set of recommendations they offered to advance future international work in middle level education. The recommendations include (a) expanding and strengthening worldwide networks of middle grades scholars; (b) building consensus around a middle grades research agenda that has an international dimension; and (c) promoting and engaging in more international scholarship that is theory-driven; uses rigorous, appropriate comparative methodologies; and draws on perspectives from cultures and countries not well represented in the literature.
Keywords: comparative education; international education; middle level education; research reviews